2022
DOI: 10.3390/su141811516
|View full text |Cite
|
Sign up to set email alerts
|

Drone-Assisted Monitoring of Atmospheric Pollution—A Comprehensive Review

Abstract: Ambient air quality is a complex issue that depends on multiple interacting factors related to emissions coming from energy production and use, transportation, industrial processes, agriculture, and waste and wastewater treatment sectors. It is also impacted by adverse meteorological conditions, pollutants concentrations, their transport and dispersion in the atmosphere, and topographic constraints. Therefore, air pollutants distribution is not uniform and their monitoring at proper temporal and spatial resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 157 publications
(209 reference statements)
0
37
0
Order By: Relevance
“…of Autonomous Hexacopter UAVs for ity Air Quality Management [43] PM2.5 2023 onitoring and forecasting using smart rrent neural network for sustainable deopment in Chennai city [44] Liquid petroleum gas, propane, CH4, H2, PM2. Review articles concerning drone-assisted air quality monitoring such as [25,51] have been published. However, available reviews focus on scientific literature and may lack technical solutions found in the patent literature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…of Autonomous Hexacopter UAVs for ity Air Quality Management [43] PM2.5 2023 onitoring and forecasting using smart rrent neural network for sustainable deopment in Chennai city [44] Liquid petroleum gas, propane, CH4, H2, PM2. Review articles concerning drone-assisted air quality monitoring such as [25,51] have been published. However, available reviews focus on scientific literature and may lack technical solutions found in the patent literature.…”
Section: Methodsmentioning
confidence: 99%
“…Although analyzing scientific literature regarding drone-assisted air pollution monitoring is not the scope of this work, some examples of scientific journal publications on this field are presented in Table 2. Review articles concerning drone-assisted air quality monitoring such as [25,51] have been published. However, available reviews focus on scientific literature and may lack technical solutions found in the patent literature.…”
Section: Rotary-wing Dronesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area for this research was the Kodungaiyur dump yard located in Chennai, Tamil Nadu, as represented in Figure 2. This landfill site is one of the largest and oldest in Chennai, span- These sensors provided a comprehensive picture of air quality conditions in the solid waste dump yard, which is critical for identifying potential health hazards and implementing appropriate mitigation measures [50][51][52]. Our data collection approach involved drones with sensors deployed at varying altitudes of 3 m, 6 m, and 9 m. The study area underwent data collection at regular intervals of 3 months, corresponding to March, June, and September within a single year 2022.…”
Section: Identification Of Study Area and Data Collectionmentioning
confidence: 99%
“…Data for remote sensing studies of heap and tailings ponds high temperatures or fire effects can be obtained by thermal sensors placed on satellites, Unmanned Aerial Vehicle (UAV), or by thermal handheld cameras (Nádudvari, 2014;Abramowicz and Chybiorz, 2019;Nádudvari et al, 2020;Nádudvari et al, 2021a). Active remote sensing techniques are also used, performing surveys from satellite radar data (Akcin et al, 2007;Jiang et al, 2011;Nádudvari, 2014;Nádudvari et al, 2020;Nádudvari et al, 2021a;Karanam et al, 2021;Yu et al, 2022) or from Light Detection and Ranging (LiDAR) data acquired from a UAV airstrike (McKenna et al, 2017;Nguyen et al, 2021;Jońca et al, 2022). With these techniques it is possible to study landslides and land subsidence due to fire.…”
Section: Introductionmentioning
confidence: 99%